Zuhal: A Portrait of Urban Individuals Through Female Perspective - Emel Uzun Yedekci (CINEJ Cinema Journal)
An apartment in the center of the metropolis, a woman living in this apartment and a cat sound that no one can hear, only the woman can hear. In the film Zuhal; the loneliness, burnout, fatigue and alienation of urban individuals are conveyed effectively with these few elements. In addition, each character in the film, which tells the stories of not only Zuhal but also her neighbors, offers an example of the metropolitan type personality. These exhausted and tired urban individuals live a life far from their inner world, alienated from themselves and their surroundings. This study focuses on the individual living in today's cities, using sociological and feminist analysis methods through the film Zuhal (2021). Present-day’s individual lives in Bauman’s “liquid modernity” which is quite different than Simmel’s “the metropolitan individual”. According to Han, an individual in present-day’s “achievement society” that is dominated by speed and positivity in late modern era, grapples with psychological problems such as depression, attention deficit, hyperactivity and burnout syndrome. Furthermore, being a woman in this society brings additional challenges to the individual. The film’s protagonist, Zuhal, is in such a psychological state; she is distant from herself, alienated from others including herself, worn, exhausted and tired. Through the study, it is emphasized that the psychological state that urban individual experiences is a consequence of the social structure rather than being an individual one.